Nursing students' willingness to respond in disasters: a cross sectional study of facilitators and barriers - Zahra Tayebi; Roohangiz Norouzinia; Zahra Moatadelro; Ashkan Farokhi Pour; Bahar Nourian (BMC, 2024)
Abstract Introduction The preparedness of the healthcare system to address emergency situations is contingent on the inclination of healthcare personnel. Nursing students can serve as valuable resources to supplement the workforce during major incidents and disasters. This study investigated the facilitators and barriers of nursing students' willingness to respond to disasters at the Alborz University of Medical Sciences in 2022. Methods In this cross-sectional descriptive study, 234 nursing students were recruited using convenience sampling. A deductive-inductive questionnaire was developed and distributed through an online self-administered survey comprising demographic information and questions on barriers, facilitators, various disaster scenarios, preferred activities, and reasons for pursuing a nursing career. Results The mean willingness scores of nursing students in response to various disasters were as follows: 3.15 for natural disasters, 2.60 for man-made disasters, 2.94 for pandemics, and 3.32 overall. Among the disaster scenarios, the earthquake response obtained the highest willingness score, while infectious disease epidemics received the lowest score. The most and least willingness to perform activities during disaster response were related to bedside care and participation in patients' personal hygiene, respectively. Key determinants of participation included the possibility of immunization and concerns for family safety. Conclusion The findings indicated that nursing students are generally willing to assist as members of the healthcare team during disasters. However, the willingness to respond to infectious disease epidemics and man-made disasters was below the norm. Concerns about family health and the risk of disease transmission were identified as primary barriers. Addressing these concerns is crucial to enhance nursing students' participation in disaster response.